Development of a Nomogram Predicting the Risk of Persistence/Recurrence of Cervical Dysplasia - Giorgio Bogani; Luca Lalli; Francesco Sopracordevole; Andrea Ciavattini; Alessandro Ghelardi; Tommaso Simoncini; Francesco Plotti; Jvan Casarin; Maurizio Serati; Ciro Pinelli; Alice Bergamini; Barbara Gardella; et al. (Vaccines, 2022)
Background: Cervical dysplasia persistence/recurrence has a great impact on women’s health and quality of life. In this study, we investigated whether a prognostic nomogram may improve risk assessment after primary conization. Methods: This is a retrospective multi-institutional study based on charts of consecutive patients undergoing conization between 1 January 2010 and 31 December 2014. A nomogram assessing the importance of different variables was built. A cohort of patients treated between 1 January 2015 and 30 June 2016 was used to validate the nomogram. Results: A total of 2966 patients undergoing primary conization were analyzed. The median (range) patient age was 40 (18–89) years. At 5-year of follow-up, 6% of patients (175/2966) had developed a persistent/recurrent cervical dysplasia. Median (range) recurrence-free survival was 18 (5–52) months. Diagnosis of CIN3, presence of HR-HPV types, positive endocervical margins, HPV persistence, and the omission of HPV vaccination after conization increased significantly and independently of the risk of developing cervical dysplasia persistence/recurrence. A nomogram weighting the impact of all variables was built with a C-Index of 0.809. A dataset of 549 patients was used to validate the nomogram, with a C-index of 0.809. Conclusions: The present nomogram represents a useful tool for counseling women about their risk of persistence/recurrence after primary conization. HPV vaccination after conization is associated with a reduced risk of CIN2+.